Alfabetização de adultos na perspectiva de educandos: experiências pessoais e sociais - Garcia, Stella de Lourdes (Universidade Federal de São Carlos, 2006)
The objective of this work was to identify and to analyze which personal and social experiences are relating to the beginning of reading and writing learning, in the perspective of adult learners. This is a qualitative inquiry, whose search involved the accomplishment of interviews half-structuralized with six learners, that they had been part in 2003 of the Program of Alphabetization, Brasil Alfabetizado , implanted in the city of São Carlos - SP, Brazil, in which we act as educator. In our theoretical referential we present the characterization of the informational society, some inequalities configured in its interior and we argue the direction of the critical alphabetization in Paulo Freires s and others authors perspective, as Henry Giroux and Ramón Flecha. We analysed the content of the interviews, the personal and social experiences in the interior of the illiteracy had been classified as no dialogic experiences, therefore they disabled the social interchange and limited learners in the personal sphere. The reading and writing learning allowed positive experiences in the personal and social sphere, making possible the recovery of self-confidence of adult learners and the transformation of some of the situations of oppression lived deeply by learners, because to learn reading and writing means the appropriation of an instrument that allows the intervention in the reality. However, we emphasize the necessity of an alphabetization practice that consider both reading of the world and reading of the word , that they privilege the dialectic between the instrumental and communicative dimension, as important stage of the social transformation, that it is only become fullfilled in communion, in dialogue. The learners also interviewed had offered reflections for educators, as well as for the elaboration of public politics in the Alphabetization and Education of Adults areas.
Adults alphabetization in the learners perspective: personal and social experiences.
Keywords: Educação de adultos; Alfabetização de adultos; Freire, Paulo, 1921-1997; Pedagogia crítica; CIENCIAS HUMANAS::EDUCACAO